2011
DOI: 10.1007/s10571-011-9741-y
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin Genetic Screening in Frontotemporal Lobar Degeneration Patients From Central Italy

Abstract: Recently, mutations in the progranulin gene (GRN) were reported to account for the vast majority of Frontotemporal lobar Degeneration (FTLD) and a growing number of reports describe the implication of this gene in the development of the FTLD pathology with a significant variation in clinical features. To better clarify the contribution of GRN mutations to Italian FTLD, we screened 381 subjects: 171 cases and 210 healthy subjects, all from Central Italy, particularly of Tuscan origins. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
2
3
0
1
Order By: Relevance
“…In line with data from studies in normal individuals [25], [26] and patients with frontotemporal lobar degeneration [27], breast [17] and ovarian cancer [18], we found that Pgrn can be easily and reliably measured in the peripheral blood employing a commercially available enzyme-linked immunosorbent assay. Pairwise comparisons of fresh vs. thawed (data not shown) and plasma vs. serum samples collected from individual patients yielded remarkably similar results, suggesting that the assay used in our study was very robust.…”
Section: Discussionsupporting
confidence: 82%
“…In line with data from studies in normal individuals [25], [26] and patients with frontotemporal lobar degeneration [27], breast [17] and ovarian cancer [18], we found that Pgrn can be easily and reliably measured in the peripheral blood employing a commercially available enzyme-linked immunosorbent assay. Pairwise comparisons of fresh vs. thawed (data not shown) and plasma vs. serum samples collected from individual patients yielded remarkably similar results, suggesting that the assay used in our study was very robust.…”
Section: Discussionsupporting
confidence: 82%
“…Our cohort of C9orf72 patients presents a high variability in age at onset, duration of the disease, familial forms, and number of affected family members, in accordance with the genetic epidemiology of Italian patients with FTD …”
Section: Discussionsupporting
confidence: 80%
“…Our cohort of C9orf72 patients presents a high variability in age at onset, duration of the disease, familial forms, and number of affected family members, in accordance with the genetic epidemiology of Italian patients with FTD. [31][32][33][34][35][36] These features reflect the incomplete and age-related penetrance of the mutation, that determines the high phenotypic heterogeneity characteristic of this pathology. As expected, there are no statistically significant differences in incidence among males and females and in the distribution of APOE e4 allele.…”
Section: Discussionmentioning
confidence: 99%
“…We developed a step-by-step algorithm for guiding genetic screening on the basis of biomarker results and clinical data, to reduce time and cost of the laboratory analysis. Specifically, the decision tree was defined according to (i) the observed frequency of genes in specific clinical phenotypes in the literature [49,[55][56][57][58], and specifically in Italian clinical series [52,[59][60][61][62][63][64][65], (ii) the direct experience of the Italian centres, and (iii) practical considerations, e.g. the high speed and low cost of a given screening procedure (i.e.…”
Section: Discussionmentioning
confidence: 99%